Reactive Oxygen Species-Mediated Apoptosis and Cytotoxicity of Newly Synthesized Pyridazin-3-Ones In P815 (Murin Mastocytoma) Cell Line - Bouchmaa, Najat; Mrid, Reda Ben; Boukharsa, Youness; Bouargalne, Youssef; Nhiri, Mohamed; Idir, Abderrazak; Taoufik, Jamal; Ansar, Mʼhammed; Zyad, Abdelmajid (Drug Research, 2019)
Background In cancer cells, the intracellular antioxidant capacity and the redox homeostasis are mainly maintained by the glutathione- and thioredoxin-dependent systems which are considered as promising targets for anticancer drugs. Pyridazinones constitute an interesting source of heterocyclic compounds for drug discovery. The present investigation focused on studying the in-vitro antitumor activity of newly synthesized Pyridazin-3(2h)-ones derivatives against P815 (Murin mastocytoma) cell line. Methods The in-vitro cytotoxic activities were investigated toward the P815 cell line using tetrazolium-based MTT assay. Lipid peroxidation and the specific activities of antioxidant enzymes were also determined.Results The newly compounds had a selective dose-dependent cytotoxic effect without affecting normal cells (PBMCs). Apoptosis was further confirmed through the characteristic apoptotic morphological changes and DNA fragmentation. Two compounds (6f and 7h) were highly cytotoxic and were submitted to extend biological testing to determine the likely mechanisms of their cytotoxicity. Results showed that these molecules may induce cytotoxicity via disturbing the redox homeostasis. Importantly, the anticancer activity of 6f and 7h could be due to the intracellular reactive oxygen species hypergeneration through significant loss of glutathione reductase and thioredoxin reductase activities. This eventually leads to oxidative stress-mediated P815 cell apoptosis. Furthermore, the co-administration of 6f or 7h with Methotrexate exhibited a synergistic cytotoxic effect.Conclusions considering their significant anticancer activity and chemosensitivity, 6f and 7h may improve the therapeutic efficacy of the current treatment for cancer.
Keywords: anticancer agent; oxidative stress; thioredoxin system; glutathione system; antioxidant enzymes